Microwave‐Assisted TBHP‐Mediated Synthesis of 2‐Amino‐1, 3, 4‐oxadiazoles in Water. Issue 42 (16th November 2020) - Kumar Sigalapalli, Dilep; Kadagathur, Manasa; Sujat Shaikh, Arbaz; Jadhav, Govinda S.; Bakchi, Bulti; Nagendra Babu, Bathini; Tangellamudi, Neelima D.
Abstract: A one‐pot synthesis of 2‐amino‐1, 3, 4‐oxadiazoles has been achieved from the corresponding isothiocyanates and hydrazides in the presence of tert‐butyl hydroperoxide (TBHP) and water under microwave irradiation. The thiosemicarbazides intermediate could be derived in   situ which underwent an intramolecular cyclodesulfurization under microwave irradiation. Apart from being simpler and green, this method offers significant advantages, such as short reaction times, economy and no requirement for a catalyst, with easy workup procedures to afford a variety of 2‐amino‐1, 3, 4‐oxadiazoles in significantly high yields (85–98 %). Spectroscopic techniques were employed to elucidate the chemical structures of the final compounds and ESI‐MS technique was employed to establish the formation of thiosemicarbazide intermediate and requirement of oxygen source for the completion of reaction and the most plausible reaction mechanism. Abstract : An economical, efficient and green reaction that makes use of water as solvent, tert ‐butyl hydroperoxide as oxidant that mediated cyclodesulfurization protocol in the absence of a catalyst for the synthesis of 2‐amino‐1, 3, 4‐oxadiazoles under microwave irradiation in short reaction times. The plausible reaction mechanism was established by intercepting and characterizing all the proposed intermediates by ESI‐MS.